Analytical solutions of (2+1)-dimensional time conformable Schrodinger equation using improved sub-equation method - Ozkan, Erdogan Mehmet; Akar, Mutlu (ELSEVIER GMBH, 2022)
In this work, the improved sub-equation method is used to get exact analytical solutions for the (2+1)-dimensional time conformable Schrodinger equation with beta-derivative. This method has been used to get generalized hyperbolic function solutions, generalized trigonometric function solutions, and rational solutions. The novel structures of solutions are illustrated when appropriate parameter values have been assigned. The physical surfaces of certain obtained solutions have been visually shown in various formats, which aids in comprehending the complicated physical phenomena of these dynamical models. The findings demonstrate the superiority of the performed method, which can be used to solve a wide range of nonlinear physical equations.
Keywords: Beta-derivative; (2+1)-dimensional time conformable; Schr?dinger equation; Improved sub-equation method; OPTICAL SOLITON PERTURBATION; CUBIC NONLINEARITY; DIFFUSION; DISPERSION; MODEL; KERR; Optics